Surgical margin and other prognostic factors of invasive vulvar squamous cell carcinoma: A clinicopathological mono-center study - Binghong Guo; Jiaqi Qiu; Yulin Wang; Nuerbiya Abula; Longyi Chen; Heqing Zhao; Yongyi Zhu; Min Zheng; Zhimin Liu; Yongwen Huang (Heliyon)
Objective: To evaluate prognostic factors in women with invasive VSCC at Sun Yat-sen University Cancer Center (SYSUCC). Methods: 137 patients with VSCC at SYSUCC were retrospectively analyzed. The Kaplan-Meier method assessed the overall survival (OS) and progression-free survival (PFS) time. Prognostic factors were identified using univariable and multivariable Cox regression analysis. Results: Only 2 out of 137 patients had positive postoperative margins after intraoperative supplemental excision. The international federation of gynecology and obstetrics (FIGO) Stage III-IV (HR: 4.67, 95 % confidence intervals (CI): 2.48–8.79) and BMI ≥25 kg/m2 (HR: 1.86, 95 % CI: 1.08–3.23) were independent risk factors for OS. The independent risk factors affecting PFS included FIGO stage III-IV (HR: 3.72, 95 % CI: 2.10–6.60), BMI ≥25 kg/m2 (HR: 2.15, 95 % CI: 1.28–3.64), and squamous cell carcinoma antigen (SCC-Ag) > 1.5 ng/ml (HR: 2.06, 95 % CI: 1.23–3.47). The survival of 12 individuals with perineural invasion (PNI) was extremely poor, with a median OS of 37 months and a median PFS of 22 months. Conclusion: The surgical margin should be at least 1.0 cm away from the tumor edge. When the surgeons cannot ensure the negative margins, detecting surgical margins with rapid pathological examination may reduce the incidence of postoperative positive margins. FIGO stage III-IV, ILN metastases, and BMI ≥25 kg/m2 are important adverse prognostic factors in VSCC patients. Cases with PNI may have poor prognosis. SCC-Ag might be a useful marker for predicting relapse.